Undergraduates held a protest against zionist regime - UMP, PNC
About 500 Universiti Malaysia Pahang (UMP) undergraduates held a rally at the compound of UMP Chancellery Building as a show of protest against the attack on Gaza, Palestine by the Zionist regime.